Corporate Social Resposibilty Implementation In Indonesia: Efforts To Protect Human Rights And Consumers - Ayunda, Rahmi (Jurnal Komunikasi Hukum, 2021)
An increase in corporate concern for the quality of people’s lives, can create social and environmental harmonization that can affect business activities. Then was born the demand for the role of the company to have Corporate Social Responsibility (CSR). This is one of the benefits companies can get from CSR activities. With the implementation of CSR in a company. The sustainability of the company will be more guaranteed, because through CSR the company has a full commitment in carrying out the mandate of the constitution and laws to improve the welfare of the community in the freedom to undergo economic practices and obtain resources for the company itself. This study aims to determine the implementation of CSR PT Aneka Tambang (ANTAM) related to Human Rights and consumers. This study uses secondary data collection techniques in the study of literature. The results of this study show respect for and protection of human rights as an inseparable part of the Company's daily operations and in interactions with stakeholders to the company's interaction with communities around the operational area. Also, ANTAM always pays attention to the quality of products produced in the production process to achieve consumers satisfaction because it realizes that customers are stakeholders who play an important role for business sustainability.